THE INFLUENCE OF SUPPLY CHAIN INTEGRATION ON ORGANIZATIONAL PERFORMANCE: FROM THE POINT OF VIEW OF ORGANIZATIONAL CAPABILITY IN INDONESIA - Hidayat, Ahmad; Nugroho, Joko; CANIAGO, ASPIZAIN; Ismail, Dingot Hamonangan; Solihin, Agung; Halim, Paisal (International Journal of Supply Chain Management, 2020)
The current research intends to analyze the implications of three aspects of supply chain integration (SCI) on three types of firm performance (FP) from the organizational capability (OC) context. The analysis examines the associations between internal integration (II), consumer integration (CI), supplier integration (SI), supplier-oriented performance (SOP), market-oriented performance (MOP), and financial condition from the organizational capacity point of view, based on the data of 670 firms in Indonesia. The structural equation model is used to carry out the analysis. The findings suggest that internal integration strengthens external integration and explicitly and implicitly increases FP through internal and external collaboration. Furthermore, complete or partial meditation between supply chain integration and FP are revealed and thus demonstrate the contradictory results regarding SCI on FP in earlier investigations.